DADBOT AND WHAT ‘HE’ REVEALS ABOUT REDDIT’S EVERYDAY PLATFORM CULTURE - Carlon, Dominique Maree (AoIR Selected Papers of Internet Research, 2023)
_u/dadbot_3000_ is one of many from a collective of DadBots that claim to bring ‘dad jokes’ and bad puns to Reddit. In practice, DadBots are better known for simply commenting ‘Hi, I’m Dad’ and together they have fostered a well-known presence and identity on the Reddit platform. The presence of bots such as _u/dadbot_3000_ demonstrate how online communities engage with semi-autonomous entities in a creative, ‘playful’ (Massanari, 2016) and sometime humorous way. Bots are frequently examined as problematic on account of their potential to distort social interaction, spread misinformation, and disrupt political process (Dubois & McKelvey, 2019; Albadi, et al., 2019; Shao et al., 2018). However bots such as _u/dadbot_3000_ can also be entertaining, engage in humour or contribute to the cultural landscape where they operate. This paper will present a cultural biography of _u/dadbot_3000_, examining its interactions with other bots and human users. A time series of events will highlight patterns across the bot’s lifespan, depicting controversies, connections, and how attitudes and interactions with the bot evolve over time. By tracing the life stories of _u/dadbot_3000_, this research will add insight into how bots, and people’s perception of them reflect, and contribute to the culture and architecture of online platform environments.